Ligand-Dependent Mechanisms of sst2A Receptor Trafficking: Role of Site-Specific Phosphorylation and Receptor Activation in the Actions of Biased Somatostatin Agonists - Kao, Yachu J. (Endocrine Society, 2011)
The somatostatin receptor subtype 2A (sst2A) mediates many of somatostatin's neuroendocrine actions and is the primary therapeutic target for the stable somatostatin analogs used to inhibit hormone secretion by pituitary and gastroenteropancreatic tumors. Two new multireceptor targeting somatostatin analogs currently under clinical investigation, the multisomatostatin receptor agonist cyclo-[diaminoethylcarbamoyl-HydroxyPro-Phenylglycine-D-Trp-Lys-(4-O-benzyl)Tyr-Phe] (SOM230) (Pasireotide) and pan-somatostatin receptor agonist Tyr-cyclo-[D-diaminobutyric acid-Arg-Phe-Phe-D-Trp-Lys-Thr-Phe] (KE108), behave as functionally selective ligands at the sst2A receptor, mimicking some of somatostatin's actions but antagonizing others. Further, SOM230 and KE108 are less able to induce receptor internalization than somatostatin, indicating that they exhibit functional selectivity for receptor regulation as well as signaling. Here, we identify agonist-specific differences in the molecular events regulating sst2A receptor endocytosis. SOM230 and KE108 were less potent and less effective than somatostatin at stimulating sst2A receptor phosphorylation at two pairs of residues, Ser341/343 and Thr353/354. Only the pattern of Thr353/354 phosphorylation correlated with receptor internalization, consistent with the known importance of Thr phosphorylation for sst2A receptor endocytosis. As expected, arrestin recruitment to membrane receptors was reduced with SOM230 and KE108. In addition, both receptor dephosphorylation and receptor recycling occurred more rapidly with SOM230 and KE108 than with somatostatin. Surprisingly, however, SOM230 and KE108 also altered sst2A internalization in a phosphorylation-independent manner, because these analogs were less effective than somatostatin at stimulating the endocytosis of a phosphorylation-negative receptor mutant. These results show that the decreased receptor internalization produced by SOM230 and KE108 compared with somatostatin result from phosphorylation-independent effects as well as reduced site-specific receptor phosphorylation and receptor-arrestin association.